Zeolite as natural gas adsorbents - Nor Kamarudin, Khairul Sozana; Mat, Hanapi; Hamdan, Halimaton (Faculty of Science, 2007)
Zeolites are inorganic crystalline materials with uniform sized pores of molecular dimensions. Many researchers have proved that zeolite has good adsorption characteristics, which has potential to be use as an adsorbent in gas separation process and adsorptive gas storage. Since 1980s, zeolite properties were found that it could be tailored and modified for specific application. The modified zeolites lead to the positive development in vast applications from catalyst, adsorbent to nanoparticle technology. This research studies the adsorptive characteristics of various adsorbents such as zeolite A, X, Y, mordenite and ZSM-5 as well as mesoporous materials such as MCM-41 and SBA-15. The study was carried out using gases such as N2, CO2, and CH4. The modifications was carried out by introducing various types of substance or modifying agent onto/into selected adsorbents using several modification methods in order to enhance the adsorptive capacity of the adsorbents. The performance of the adsorbents for adsorptive natural gas storage was also investigated. The structures of the adsorbents were characterized by powder X-Ray Diffraction (XRD), Micromeritics ASAP 2000, Fourier Transform Infrared (FTIR) spectroscopy and Scanning Electron Microscope (SEM). The adsorption equilibrium and kinetic study of gases on the modified samples have been analyzed using Thermogravimetric Analyzer (TGA). Gas adsorption characteristics of zeolites were evaluated based on the adsorption capacity, adsorption isotherms, heat of adsorption, uptake rate of the adsorbates, and FTIR spectra of gas-zeolite interactions. It was found that cage-type zeolites such as NaX and NaY are better adsorbents than channel-type zeolites. Results also revealed that types of metal cation, metal oxide, amine, loading concentration, calcination temperature, duration of calcination process, adsorption temperature and pressure as well as the modification techniques greatly affect the modified zeolite adsorbent structural and gas adsorption characteristics. In general, modification can enhance the adsorption characteristics of adsorbents. The adsorption measurements have revealed that exchanging Na+ with some metal cation enhanced the adsorption capacity of methane. The addition metal oxides can also increases the adsorption of gases. Addition of MgO to NaY increases the adsorption capacity of CO2, meanwhile, HgO-NaY has higher adsorption of N2 and CH4 than NaY itself. The study also showed that CO2 adsorption on microporous and mesoporous silica improved as amine grafted onto its surface. The isosteric heat of adsorption that measured using TGA and gases adsorption bands that observed in FTIR spectra also demonstrate that the adsorbates interact with adsorbents. At higher pressure (up to 500 psi), the study showed that in order to get high methane storage and delivery capacity, adsorbents with large accessible surface area, high pore volume and high packing density are needed. Amount of methane remain adsorbed after discharging was influence by the adsorbent pore volume. These findings enable us to elucidate the fundamental question about the structural and adsorptive characteristics of natural gas on modified zeolites as well as other porous materials such as MCM-41 and SBA-15.